Minding The Gap: Range Size And Economic Use Drive Functional Trait Data Shortfall In The Atlantic Forest - Petisco-Souza, Ana Carolina; Fernanda Thiesen Brum; Marcilio-Silva, Vinícius; Zwiener, Victor P; Zanella, Andressa; Dias, Arildo S; González-Melo, Andrés; Jansen, Steven; Mazzochini, Guilherme G; Niinemets, Ülo; Pillar, Valério D; Sosinski, Enio; et al. (bioRxiv, 2020)
ABSTRACT Biodiversity shortfalls are knowledge gaps that may result from uneven sampling through time and space and human interest biases. Gaps in data of functional traits of species may add uncertainty in functional diversity and structure measures and hinder inference on ecosystem functioning and ecosystem services, with negative implications for conservation and restoration practices, such as in Atlantic Forest hotspot. Here we investigate which are the potential drivers of trait data gaps and where geographically they are in the Atlantic Forest. We quantified trait gaps for four key plant functional traits of 2335 trees species, and evaluated which factors drive trait gap at the species and at the geographical level. At the species level, we found larger trait gaps for small-ranged and with no economic use. At the geographical level, we found larger gaps at the Atlantic Forest east coast. Trait gaps were higher away from urban areas, and among species with smaller mean range size and smaller mean economic use of wood, and smaller near protected areas. Efforts on reducing trait gaps of small-ranged and of species with economic use of wood can further advance theory-driven studies and improve knowledge coverage Competing Interest Statement The authors have declared no competing interest.